2014
DOI: 10.1186/s12870-014-0284-5
|View full text |Cite
|
Sign up to set email alerts
|

cDNA-AFLP analysis reveals the adaptive responses of citrus to long-term boron-toxicity

Abstract: BackgroundBoron (B)-toxicity is an important disorder in agricultural regions across the world. Seedlings of ‘Sour pummelo’ (Citrus grandis) and ‘Xuegan’ (Citrus sinensis) were fertigated every other day until drip with 10 μM (control) or 400 μM (B-toxic) H3BO3 in a complete nutrient solution for 15 weeks. The aims of this study were to elucidate the adaptive mechanisms of citrus plants to B-toxicity and to identify B-tolerant genes.ResultsB-toxicity-induced changes in seedlings growth, leaf CO2 assimilation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 123 publications
6
33
1
Order By: Relevance
“…The expression of cytochrome P450s ( CytoP450s ) was increased in Vicia sativa seedlings when exposed to plant hormone methyl jasmonate (Pinot et al, 1998 ) and in B-toxic C. grandis leaves (Guo et al, 2014 ). Transgenic tobacco and potato plants over-expressing CytoP450 displayed increased monooxygenase activity and enhanced tolerance of oxidative stress after herbicide treatment (Gorinova et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of cytochrome P450s ( CytoP450s ) was increased in Vicia sativa seedlings when exposed to plant hormone methyl jasmonate (Pinot et al, 1998 ) and in B-toxic C. grandis leaves (Guo et al, 2014 ). Transgenic tobacco and potato plants over-expressing CytoP450 displayed increased monooxygenase activity and enhanced tolerance of oxidative stress after herbicide treatment (Gorinova et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the capacity to bind ATP and NADPH (Cervilla et al 2009a) and limit the availability of energy and reduce power, respectively, which are necessary for carbohydrate synthesis in the light-independent reactions of the Calvin-Benson cycle. Therefore, changes in sugar content and partitioning (Roessner et al 2006;Papadakis et al 2018), as well as in carbon skeleton devoted to aminoacids, which are strictly interlinked (Guo et al 2014) can be observed as a response to B excess (Sang et al 2015;Ayvaz et al 2016). An imbalance of C/N ratio also promote phenomena of early senescence (Lo Piccolo et al 2018;Sotiras et al 2019) and this explains the enhancement of senescence-related hormones i.e.…”
Section: Physiological and Biochemical Responses To B Excessmentioning
confidence: 99%
“…Boron toxicity has been shown to affect several developmental or biochemical processes in plants ( Sakamoto et al, 2011 ), including inhibiting the formation of glutathione ( Ruiz et al, 2003 ) and tocopherol ( Keles et al, 2004 ), reducing root cell division ( Aquea et al, 2012 ), and shoot cell wall expansion ( Loomis and Durst, 1992 ), decreasing fruit number, size and weight, formatting reactive oxygen species(ROSs) ( Paull et al, 1992 ; Nable et al, 1997 ; Karabal et al, 2003 ; Cervilla et al, 2007 ), increasing oxidative damage ( Gunes et al, 2006 ; Molassiotis et al, 2006 ; Sotiropoulos et al, 2006 ), affecting the photosynthesis and antioxidant apparatus ( Landi et al, 2013 ), and leading to DNA damage ( Sakamoto et al, 2011 ). A cDNA-AFLP analysis revealed that long-term boron stress induced changes related to signal transduction, metabolism of carbohydrate, energy, nucleic acid, protein, amino acid and lipid, cell wall and cytoskeleton modification, stress responses, and cell transport in Citrus grandis and Citrus sinensis ( Guo et al, 2014 ). Furthermore, several genes involved in plant tolerance to boron stress have been identified, including Arabidopsis thaliana BOR4 and TIP5;1 ( Miwa et al, 2007 ; Pang et al, 2010 ), barley ( Hordeu mvulgare ) Bot1 ( Sutton et al, 2007 ), wheat and barley HvBOR2 ( Reid, 2007 ), and citrus ( Citrus macrophylla ) CmBOR1 ( Cañon et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%